Impact evaluation of the Health Sector Reform in Costa Rica - Rosero Bixby, Luis (2004)
Health Sector Reform was implemented gradually across Costa Rica in a sort of natural experiment that offers an opportunity to evaluate its impact. Assuming a quasi experimental evaluation design, this is an analysis of mortality trends in the country’s 420 districts (minor civil divisions) during the period between 1985 and 2001, applying multivariable regression models. The models estimated that reform adoption reduced childhood mortality by 8% and adult mortality by 2%. The effect was 14% on adult mortality due to communicable diseases, none due to those of social origin, and was similar to the total (2%) due to chronic diseases. These effects significantly increased with time since reform adoption, in a sort of dose-response effect. Translating these results into lives saved shows that approximately 120 children’s lives and 350 adult lives were saved in 2001. The reform was applied first to the most disperse and least socio-economically developed zones, which reduced the equity-in-services gap at the primary health care level. Health sector reform, which started to be implemented in 1995, is possibly the most important event for public health in Costa Rica during the last decade, since it allowed renewed progress on the path to development after a long stagnation. Life expectancy rose from 76.2 to 77.7 years between 1995 and 2000.